Expression Profile of Sonic Hedgehog Pathway Members in the Developing Human Fetal Brain - Julia Tichy (BioMed Research International, 2015)
The Sonic Hedgehog (SHH) pathway plays a central role in the developing mammalian CNS. In our study, we aimed to investigate the spatiotemporal SHH pathway expression pattern in human fetal brains. We analyzed 22 normal fetal brains for Shh, Patched, Smoothened, and Gli1-3 expression by immunohistochemistry. In the telencephalon, strongest expression of Shh, Smoothened, and Gli2 was found in the cortical plate (CP) and ventricular zone. Patched was strongly upregulated in the ventricular zone and Gli1 in the CP. In the cerebellum, SHH pathway members were strongly expressed in the external granular layer (EGL). SHH pathway members significantly decreased over time in the ventricular and subventricular zone and in the cerebellar EGL, while increasing levels were found in more superficial telencephalic layers. Our findings show that SHH pathway members are strongly expressed in areas important for proliferation and differentiation and indicate a temporal expression gradient in telencephalic and cerebellar layers probably due to decreased proliferation of progenitor cells and increased differentiation. Our data about the spatiotemporal expression of SHH pathway members in the developing human brain serves as a base for the understanding of both normal and pathological CNS development.